Bacteriology in Adenoid Disease - Salami, Azzam M.; Yousef, Raid Y.; faza’a, Sua’ad A.; Yousef, Roaida Y. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Adenoidal hypertrophy is generally considered a common condition of childhood .When obstructive symptoms or recurrent otitis media (suppurative or non suppurative) occurs, adenoidectomy is generally indicated.A wide range of bacteria could be isolated from the surface and core tissue of the removed adenoid tissue. Patients and Methods: A prospective study carried out in the ENT Department of AL-DIWANIYAH Teaching Hospital between October 2007 and September 2008.Involved 73 patients between 3 and 7 years, they were 31 male and 42 female .All patients underwent adenoidectomy .Surface and core swabs was taken from all specimens and submitted to bacteriological study. Results: Pathogens were detected in (83.56%) of core specimens versus (46.57%) in surface swab cultures. β -hemolytic streptococcus was the most commonly grown organism in the core of the adenoid and/or surface culture. Resistance was shown to the commonly used antibiotics by most of the isolated pathogens. Conclusion: β -hemolytic streptococcus is the most common isolated organism in patients with adenoidal hypertrophy followed by Staphylococcus aureus, Streptococcus pneumonia then Haemophilus influenzae. Most of the isolated strains show resistance to the commonly used antibiotics.